Perbandingan Indeks def-t pada Anak Berkebutuhan Khusus Usia 6-9 Tahun di SDLB Kota Kediri: Comparison of def-t Index in Children with Special Age 6-9 Years in SDLB Kediri City - Tias , Richa; Nadira, Rahma; Kusumastiti, Anisa; Pangestu, Cantika (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2025)
Background: Dental caries is a problem in the field of oral health that is widely suffered by the Indonesian people, especially in school-age children, namely 6-9 years. Dental caries in normal children aged 6-9 years reaches 92.6%, while in children with special needs it reaches 24%, which is obtained from the calculation of the def-t index (decayed exfoliation filling) to determine the number of deciduous teeth that have caries. Children with special needs, especially deaf and intellectual disability children are more susceptible to caries because they have limitations in themselves and need special attention regarding how they maintain their oral health. Purposive: This study aims to determine the comparison of def-t index in children with disabilities (deaf and intellectual disability) aged 6-9 years in SLB Kediri City. Methods: The type of research used is analytical observational with a cross sectional approach and sampling in this study by Total Sampling, namely sampling using the entire population in implementation of study according to the inclusion criteria. The samples in this study were 10 deaf children and 10 children with intellectual disability. Results: The results of the Mann-Whitney hypothesis test revealed a comparison related to the def-t index in deaf and retarded children aged 6-9 years. Statistical analysis using Mann-Whitney test obtained a significance value (p<0.05). Conclusion: There is a comparison of def-t index in children with special needs, especially deaf children and children with dementia aged 6-9 years in SLB Kediri City. Keywords: def-t Index, Special Need Children